State-of-the-art review on the influence of crumb rubber on the strength, durability, and morphological properties of concrete - Moolchandani Karan; Sharma Abhay (Science and Engineering of Composite Materials, 2025)
Using crumb rubber (CR) from end-of-life tyres in concrete offers a practical way to reduce environmental waste while enhancing specific performance characteristics. This review brings together current findings on how CR affects the fresh properties, strength, durability, and microstructure of concrete. It explains how untreated rubber often reduces compressive strength, especially at higher replacement levels, due to poor bonding and internal voids. However, this performance drop can be significantly reduced through surface treatments like alkali washing and the use of supplementary cementitious materials. These combinations help restore strength, improve resistance to chloride attack and freeze–thaw cycles, and lower permeability. Microstructural studies show that refining particle size and improving the rubber–cement interface lead to a denser and more cohesive matrix. A classification system is proposed to guide practical applications based on the amount of rubber used and the required mechanical and durability properties. When properly designed, rubberized concrete can reduce embodied carbon by up to 25% and eliminate the need for natural aggregates in many applications. The review also outlines areas that need further attention, including long-term performance validation, lifecycle modeling, and development of practical mix design standards to support the wider use of rubberized concrete in construction.